Non-isothermal crystallization from the melt of sulfonated poly(ethylene terephthalate) - Ostrowska-Gumkowska, B.; Ostrowska-Czubenko, J. (Polimery, 2010)
The influence of copolymerization on the basic parameters of the nonisothermal crystallization process from the melt (Figs. 1,4), and also on the melting behavior (Fig. 7) of anionically modified polyethylene terephthalate) (K-X/SPET, Table 1) containing 1.9 - 10.1 % mol sulfonate groups has been studied. The obtained samples were studied by differential scanning calorimetry. It was observed that the crystallization process (Figs. 2, 3, 5, 6) and melting (Fig. 7) are crucially dependent on the structure of the chemical chain of the copolyester and the cooling rate of the polymer melt. The kinetic parameters for the crystallization process were determined by the Khanna and Liu method while the activation energy for the process according to the Kissinger method. The influence of concentration of ionic groups and the association phenomenon of these groups on the crystallization process (Tables 2, 4-6) as well as the melting of the studied ionic polymers (Tables 3, 7) was discussed.